Hedonic Price Function Estimation for Mobile Phone in Iran - Mostafavi, Sayed Mahdi; Roohbakhsh, Somaye Sadat; Behname, Mehdi (International Journal of Economics and Financial Issues, 2012)
The aim of this paper is the survey of mobile price determinants by hedonic model. We have applied the hedonic price model for mobile phone market in Iran in the year of 2008. The brands conclude NOKIA, QTEK, HTC, MOTOROLA, SONY ERICSSON and SAMSUNG that comprise 193 types of handset mobile phone. The results show that in the hedonic function, the maximum amount of parameters of hedonic price function related to the following variables respectively: touch screen, hands free and connectivity tools, and the minimum amount of them are belonged to clarification of monitor images, phone volume and phone memory. Moreover, except Motorola brand the type of brand has not a significant parameter in the hedonic price function. Keywords: Hedonic Price Model; Mobile Phone Brands; Iran JEL Classifications: C43; C51; O18